Neuroinvasive Onchocerca lupi Infection in a Ten-Year-Old Girl. (5th December 2022) - Bowers Wu, Dorothy; Ko, Brandon; Lopez Hernandez, Gloria; Botros, James; Spader, Heather; Sapp, Sarah; Qvarnstrom, Yvonne; Paddock, Christopher D.; Cantey, Paul T.; Dehority, Walter
Abstract : The nematode Onchocerca lupi is an emerging human pathogen. Though its life cycle is not well studied, it likely infects humans after a bite from a black fly vector, which in turn acquires infective microfilariae from an infected canid. These microfilariae mature into an infective larval stage within the fly. Among six reported cases in the United States, five involved children, and all occurred in the southwest. In this report, we present a case of O. lupi infection with cervical spine invasion in a healthy 10-year-old girl. She presented with five months of neurological symptoms from a rural and medically underserved area, highlighting a need for clinical vigilance in such settings for this emerging infectious threat in the American southwest.